PENGARUH KOMPETENSI SOSIAL GURU TERHADAP HASIL BELAJAR SISWA (di SMA Muhammadiyah 1 Semarang) - Lia Lu’lu’ul Lutfiyah; Eni Winaryati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Teachers are professional educators with the primary task of educating, teaching, guiding, directing, training, assessing, and evaluating students. The problem of this research is how the relation of teacher's social competence with student's learning result. The purpose of this research is to know the influence of teacher's social competence on student learning result. The research method used is descriptive qualitative method with data collection technique that is questioner, observation, interview, and documentation. The results showed that the influence of the teacher's social competence on the students' learning outcomes was proven by many studentswho were concerned, could do the exercises given by the teachers, and theaverage score was good. Keywords: Social Competence, Student's Result, Qualitative